2002
DOI: 10.1161/01.cir.0000014211.47830.4d
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Calcineurin and Sarcolemmal Ca 2+ Influx Protects Cardiac Morphology and Ventricular Function in K v 4.2N Transgenic Mice

Abstract: Background-Cardiac-targeted expression of truncated K v 4.2 subunit (K v 4.2N) reduces transient outward current (I to ) density, prolongs action potentials (APs), and enhances contractility in 3-to 4-week-old transgenic mice. By 13 to 15 weeks of age, these mice develop severely impaired cardiac function and signs of heart failure. In this study, we examined whether augmented contractility in K v 4.2N mice results from elevations in intracellular calcium ([Ca 2ϩ ] i ) secondary to AP prolongation and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 39 publications
1
44
0
1
Order By: Relevance
“…In rat ventricular myocytes, LY29 and LY30 inhibit the Kv1.5/2.1 potassium channels . Inhibition of potassium channels often results in changes in intracellular calcium levels (Tokuno et al, 1999;Doi et al, 2000;Tahara et al, 2001;Sah et al, 2002;Wang et al, 2006). Despite of the complexity of potassium channels and the coupling of intracellular potassium versus calcium concentration changes in cardiomyocytes, we have found that a general potassium channel blocker TEA inhibited CT from increasing [Ca 2+ ] i and inducing COX-2 expression.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In rat ventricular myocytes, LY29 and LY30 inhibit the Kv1.5/2.1 potassium channels . Inhibition of potassium channels often results in changes in intracellular calcium levels (Tokuno et al, 1999;Doi et al, 2000;Tahara et al, 2001;Sah et al, 2002;Wang et al, 2006). Despite of the complexity of potassium channels and the coupling of intracellular potassium versus calcium concentration changes in cardiomyocytes, we have found that a general potassium channel blocker TEA inhibited CT from increasing [Ca 2+ ] i and inducing COX-2 expression.…”
Section: Discussionmentioning
confidence: 88%
“…Inhibition of potassium channels often lead to changes in intracellular calcium (Tokuno et al, 1999;Doi et al, 2000;Tahara et al, 2001;Sah et al, 2002;Wang et al, 2006) (Fig. 9A).…”
Section: Ct Causes An Increase In Intracellular Calciummentioning
confidence: 99%
“…Heart-to-body weight ratios were unchanged in Iso ϩ Ver and decreased in Ver-only pumps. Ver has been shown to prevent increases in heart-to-body weight ratio observed in hypertrophy models (34,42), and a decreased ventricular wet weight was demonstrated in chicken embryos treated with Ver (10). Despite similar, albeit unexpected, increases in HR by either Ver or Iso alone, Iso ϩ Ver antagonized the Ver-induced increase of Ca 2ϩ channels.…”
Section: Discussionmentioning
confidence: 99%
“…Preventing excessive I to,f reductions may be of critical importance because changes in I to,f can lead to altered electrical and contractile properties of the myocardium, which may contribute to impaired pump function and arrhythmias (6, 48 -51). For example, we (48,52) and others (53) have shown previously that not only is I to,f an important determinant of action potential profile changes occurring in heart disease and regional differences in action potential profile, but I to,f is also a major regulator of the amplitude and kinetics of cardiac contraction in rodents and larger mammals by modulating Ca 2ϩ entry via L-type Ca 2ϩ channels. Thus, Cn activation not only induces hypertrophy, but also modulates the extent of the electrical and contractile changes induced as a result of I to,f reduction caused by hypertrophic stimuli.…”
Section: Non-transgenic Micementioning
confidence: 92%